Development of German Neurosurgical Health Care from 1945 to 1955 - Steudel, Wolf-Ingo; Collmann, Hartmut; Reulen, Hans-Jürgen (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2025)
In Germany, the idea of neurosurgery as a separate medical specialty emerged in the 1920s in response to Cushing's role model, but can in part also be attributed to the preceding decades of German brain research. First attempts of professional emancipation failed due to political conditions. During National Socialism, the military significance of neurosurgical expertise was recognized. Only after World War II, the advancement of the new specialty gathered pace by the spread of multiple new specialized units. It is worth mentioning that apart from a nationwide coverage with neurosurgical health care the academic recognition of the specialty has also been fully achieved with regard to medical care, research, and teaching.
Keywords: health care; medical education; neurosurgical specialization; board certification; scientific council (Wissenschaftsrat); division of Germany